Deep-blue organic light-emitting diodes based on push-pull π-extended imidazole-fluorene hybrids. (January 2021) - Chen, Guowei; Qiu, Zhipeng; Tan, Ji-Hua; Chen, Wen-Cheng; Zhou, Peiqi; Xing, Longjiang; Ji, Shaomin; Qin, Yanlin; Zhao, Zujin; Huo, Yanping
Abstract: Four donor-π-acceptor (D-π-A) luminophores based on π-extended imidazole-fluorene hybrid, namely PhIF-1, PyIF-1, PhIF-2 and PyIF-2, are developed. Two imidazole derivatives, phenanthreneimidazole (PhI) and pyreneimidazole (PyI), are investigated to highlight their potential applications in deep-blue electroluminescence. A mild electron pull-push system between PhI/PyI and fluorene is achieved, enabling the mixture of locally excited (LE) and charge transfer (CT) excited state character. Systematic study is also carried out to reveal the influence of n-hexyl chain at the 9-position of fluorene on the photophysical properties of these new emitters. We find that the introduction of alkyl chain can tune photophysical properties, leading to better solid-state emission in PhIF-2 and PyIF-2 . All the new compounds show intense high-energy fluorescence with excellent thermal properties suitable for organic light-emitting diode (OLED) application. Non-doped OLEDs exhibiting maximum external quantum efficiency (EQE) of 3.65% and 3.75% are realized using PhIF-1 and PyIF-1, respectively. Compared with PhIF-1 and PyIF-1, alkyl chain substituted PhIF-2 and PyIF-2 exhibit better blue color purities of (0.15, 0.12) and (0.15, 0.13), respectively. In addition, better color purity and higher luminescence efficiency are acquired simultaneously in doped devices. An OLED employing 20 wt% PyIF-1 as emitting core displays a high EQE of 4.29% at 1000 cd m −2 (EQEmax  = 4.60%). This work may provide a rational design for π-extended imidazole D-π-A luminophores for deep-blue electroluminescence applications. Graphical abstract: Image 1 Highlights: Four bipolar π-extended imidazole-fluorene hybrids have been designed and synthesized. Moderate push-pull molecular framework enables the mixture of locally excited and charge transfer excited state. The non-conjugated n -hexyl chain can unexpectedly tune the photophysical properties via aggregation disturbance. Efficient deep-blue OLEDs with slow roll-off were achieved with the new emitters.